'Everything's fine, so why does it happen?' A qualitative investigation of patients' perceptions of noncardiac chest pain. Issue 13 (19th May 2015) - Webster, Rosie; Thompson, Andrew R; Norman, Paul
<x xml:space="preserve">Abstract</x> Aims and objectives To examine patients' perceptions and experiences of noncardiac chest pain, within the framework of the common sense model. Background Patients with noncardiac chest pain have good physical prognosis, but frequently suffer prolonged pain and psychological distress. The common sense model may provide a good framework for examining outcomes in patients with noncardiac chest pain. Design Qualitative thematic analysis with semi‐structured interviews. Methods In 2010, participants recruited from an emergency department (N = 7) with persistent noncardiac chest pain and distress were interviewed using a semi‐structured schedule, and data were analysed using thematic analysis. Results Seven themes were identified; six of which mapped onto core dimensions of the common sense model (identity, cause, timeline, consequences, personal control, treatment control). Contrary to previous research on medically unexplained symptoms, most participants perceived psychological factors to play a causal role in their chest pain. Participants' perceptions largely mapped onto the common sense model, although there was a lack of coherence across dimensions, particularly with regard to cause. Conclusion Patients with noncardiac chest pain lack understanding with regard to their condition and may be accepting of psychological causes of their pain. Relevance to clinical practice Brief psychological interventions aimed at improving understanding of the causes of noncardiac chest pain and providing techniques for managing pain and stress may be useful for patients with noncardiac chest pain.